1998
DOI: 10.1111/j.1399-0039.1998.tb03058.x
|View full text |Cite
|
Sign up to set email alerts
|

Haplotypes comprising subtypes of the DQB1*06 allele direct the antibody response after immunisation with hepatitis B surface antigen

Abstract: Two HLA class II haplotypes, HLA-[DQB1*0602; DQA1*0102; DR15] and HLA-[DQB1*0603; DQA1*0103; DRB1*1301] were found to be less common in 52 nonresponders compared with 68 responders, P<0.025 and P<0.05 respectively, after vaccination with hepatitis B surface antigen (HBsAg). Another haplotype, HLA-[DQB1*0604; DQA1*0102; DRB1*1302], had a significantly higher frequency in the nonresponders (P<0.005). The nonresponders and responders were nonsmoking, healthy individuals with an antibody concentration of <10 IU/l … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…22 Furthermore, in a recent report, Val 86 of the HLA-DR␤ chain was postulated to also determine the response against hepatitis B surface antigen. 23 In this study, HLA-DRB1*1301 and HLA-DR15 alleles were found as the responder alleles, but HLA-DRB1*1302 was associated with nonresponse to hepatitis B surface antigen. Additional evidence for the role of position 86 of the HLA-DR␤ chain in controlling immune responses came from studies performed in Gambia, West Africa.…”
Section: Discussionmentioning
confidence: 83%
“…22 Furthermore, in a recent report, Val 86 of the HLA-DR␤ chain was postulated to also determine the response against hepatitis B surface antigen. 23 In this study, HLA-DRB1*1301 and HLA-DR15 alleles were found as the responder alleles, but HLA-DRB1*1302 was associated with nonresponse to hepatitis B surface antigen. Additional evidence for the role of position 86 of the HLA-DR␤ chain in controlling immune responses came from studies performed in Gambia, West Africa.…”
Section: Discussionmentioning
confidence: 83%
“…Individuals responding to vaccination with the induction of a high anti-HBsAg titer showed a strong T cell response non-responsiveness (HBsAg titer < 10 kU/L) to vaccination are associated with certain human leukocyte antigen (HLA)-class Ⅱ alleles. DRB1*0301, DRB1*0701, and DQB1*0201 [5,8,9] were shown to have a higher prevalence in non-responders, whereas other antigens (DRB1*0101, *1301, *1501, and DPB1*0401) seem to mediate strong immune responses [9][10][11][12] . Higher age, obesity, male gender, smoking, and chronic dialysis are risk factors for a non-/ low-responsiveness [8,9,[13][14][15] .…”
Section: Resultsmentioning
confidence: 99%
“…In many of the non-responders not explained by the above risk factors, certain HLA types have been found to be associated with non response [16][17][18][19] . The relationship of hepatitis B vaccination response with age is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…A non-response was defined as mean antiHBs antibody titers below 10 IU/L, low responders were those with titers between 10-99 IU/L, and those with anti-HBs titers more than 100 IU/L [13][14][15][16][17][18][19][20][21][22][23][24][25][26] were responders. A high response was on with titers more than 1 000 IU/l.…”
Section: Hbv Vaccination and Sample Collectionmentioning
confidence: 99%